2021
DOI: 10.3389/fendo.2021.661305
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamus-Pituitary Dysfunction as an Independent Risk Factor for Postoperative Central Nervous System Infections in Patients With Sellar Region Tumors

Abstract: ObjectiveThe purpose of this study was to verify that hypothalamus-pituitary dysfunction is one of the risk factors for postoperative central nervous system infections (PCNSIs).MethodWe performed a retrospective analysis of all patients with sellar region lesions who underwent surgery between January 2016 and November 2019 at Peking Union Medical College Hospital. In total, 44 age− and sex-matched controls were enrolled. Univariate and multivariate analyses were performed to identify risk factors for PCNSIs.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The case of our patient, together with others [14][15][16][18][19][20], suggests that the high frequency of infectious events may not be exclusively iatrogenic but also a direct consequence of the underlying disease. The increased use of antimicrobial agent even before the steroid therapy [16] and the presence of infection events as a co-diagnosis at the first diagnosis of the disease [17] strengthen our hypothesis.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The case of our patient, together with others [14][15][16][18][19][20], suggests that the high frequency of infectious events may not be exclusively iatrogenic but also a direct consequence of the underlying disease. The increased use of antimicrobial agent even before the steroid therapy [16] and the presence of infection events as a co-diagnosis at the first diagnosis of the disease [17] strengthen our hypothesis.…”
Section: Discussionsupporting
confidence: 59%
“…The involvement of this latter tract can be insidious as abdominal symptoms overlap adrenal crisis. Furthermore, it was shown that adrenal insufficiency is an independent risk factor for the development of central nervous system infections following neurosurgical removal of sella turcica tumours [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sellar region, one of the most complex neoplastic areas of the brain, can give rise to a wide variety of pathologically distinct tumors, including pituitary adenoma, germ cell tumor, Rathke’s cleft cyst, meningioma, chordoma, craniopharyngioma, etc. ( 18 ). Most of these tumors, especially craniopharyngiomas, are often accompanied by calcification; however, pituitary adenomas with calcification are scarcely rare ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of intracranial infection after neurosurgery can vary from 0.7 to 8.9%, as reported in different studies. [1][2][3][4] This discrepancy may derive from the choice of different diagnostic criteria, the presence of multiple clinical factors that may interfere with the prognosis, and regional differences. China has the largest population in the world, and the highest number of craniotomies is performed in China.…”
Section: Introductionmentioning
confidence: 99%